Using Hawthorn as a Promising Rootstock for Plums - Noori, Ibrahim M. (Sulaimani Journal for Pure and Applied Sciences, 2014)
This study was conducted during 2011, at Darbandi Zirgwez, locating between some peaks of Gilazarda mountain, Sulaymaniyah, Kurdistan Region-Iraq. The local variety of plum (Haluzha Qadiri) was used as scion and hawthorn trees grown naturally in the region as rootstock. Two budding methods (T-budding and pipe-budding) performed during three dates (mid May, early June and mid June). A factorial randomized complete block design with three replications, twenty buds per replication and the least significant difference test (LSD, P≤ 0.05) were used for means separation. The percents of bud-take successes were recorded after two months from budding times, whereas the observations on subsequent growth parameters were recorded at the end of the season. Pipe budding gave the higher significant values of budding success (67.82%) and scion growth diameter (8.88 mm). Budding on mid-May resulted in signigicant values of budding success (65.42%), scion growth length (15.75 cm) and the number of leaves per scion growth (14.57). The maximum value of percent budding success (81.8%) was recorded when pipe- budding was done on mid-May. In addition, significant differences in the length (16.2 cm) and diameter (8.93 mm) of scion growths, and the number of leaves per scion growth (16.03) were resulted from the same interaction.
Keywords: Pipebudding; Tbudding; plum; hawthorn; natural rootstock